Differences in dietary fibre intake and associated familial factors in a longitudinal study at two time points across adolescence. Issue 14 (6th October 2020) - Swann, Olivia G; Breslin, Monique; Kilpatrick, Michelle; O'Sullivan, Therese A; Oddy, Wendy H
Abstract: Objective: Dietary fibre is essential for a healthy diet; however, intake is often inadequate. Understanding of sources of dietary fibre and familial factors associated with intake in adolescents is limited, hampering efforts to increase intake. We aimed to determine adequacy of dietary fibre intake in adolescents, examine how intake changes from mid to late adolescence, identify major food sources and explore associations with familial factors. Design: Dietary fibre intake measured with semi-quantitative FFQ and sources calculated with the AUSNUT database. Familial factors determined by questionnaire. Setting: Western Australian Pregnancy Cohort (Raine) Study. Participants: Generation 2 adolescents from the 14- ( n 1626) and 17-year ( n 835) follow-ups. Results: Mean intake of dietary fibre did not meet national dietary guidelines other than for females aged 14 years. Mean intake of both sexes was lower at 17 years (23·0 (sd 10·0) g/d) than at 14 years (24·3 (sd 9·0) g/d, P < 0·001). The quantity of dietary fibre consumed per megajoule also decreased (2·6 (sd 0·7) g/MJ at 14 years, 2·5 (sd 0·9) g/MJ at 17 years, P = 0·007). The greatest source of dietary fibre was cereals and grains, followed by fruits, then vegetables. In multivariable mixed-model analysis, female sex, Caucasian race, age 14 years, good family functioning, high level of parental education and high energy intake were independently associated with higher dietary fibre intake. Conclusions: Our study highlights an age range and characteristics of adolescents lacking in dietary fibre, thereby identifying target populations for interventions to improve dietary fibre intake across adolescence, which would lead to better health.